Primary cutaneous centrofollicular lymphoma with a good response to radiotherapy - Cláudia Medeiros dos Santos Camargo; Lislaine Bomm; Leonardo Spagnol Abraham; Rafael Daher; Maria de Fátima Guimarães Scotelaro; Luna Azulay Abulafia (Sociedade Brasileira de Dermatologia, 2013)
Primary cutaneous lymphomas have different clinical behavior and prognosis than systemic lymphomas of similar histological subtype. About 30% of non-Hodgkin lymphomas involve extranodal tissues, the skin being the second most affected body organ after the gastrointestinal tract (approximately 18%). According to the EORTC (European Organization for Research and Treatment of Cancer) classification, the lymphoma centrofollicular is indolent, since the lesions increase in size slowly over the years and spread to extracutaneous sites is uncommon. Based on this, radiotherapy has been considered the treatment of choice by many studies. We present the case of a patient who had cutaneous centrofollicular scalp lymphoma for 1 year and showed good response to radiotherapy.